Increased acute immune response during the meningo-encephalitic stage of Trypanosoma brucei rhodesiense sleeping sickness compared to Trypanosoma brucei gambiense. Issue 6 (March 2015) - Tiberti, Natalia; Lejon, Veerle; Mumba Ngoyi, Dieudonné; Matovu, Enock; Enyaru, John; Walter, Nadia; Fouda, Catherine; Lutumba, Pascal; Kristensson, Krister; Bisser, Sylvie; Mathu Ndung'u, Joseph; Büscher, Philippe; et al.
Graphical abstract: Highlights: Cerebrospinal fluid from gambiense and rhodesiense HAT patients was compared. Trypanosoma brucei rhodesiense brain infection evokes a strong activation of the innate immunity. CSF C-reactive protein discriminates between gambiense and rhodesiense HAT. Abstract: The host central nervous system (CNS) response to infection with Trypanosoma brucei ( T . b .) gambiense or T . b . rhodesiense parasites, the causing agent of human African trypanosomiasis (HAT), is a poorly explored area. The two parasites are responsible for respectively a chronic and an acute form of HAT. In both cases, however, the disease progresses from a haemolymphatic first stage (S1) to a meningo-encephalitic second stage (S2) due to the penetration of parasites into the CNS. In the present study, we investigated and compared the cerebrospinal fluid (CSF) from S2 patients affected by either T . b . gambiense or T . b . rhodesiense HAT, using a mass spectrometry quantitative proteomics approach. Gene ontology and pathway analyses on the 222 quantified human proteins revealed a predominant activation of the innate immune and the acute phase responses in rhodesiense HAT patients. These results were further confirmed through the verification of the over-expression of two proteins involved in these mechanisms, C-reactive protein (CRP) and orosomucoid 1 (ORM1), in 126 S2 HAT patients suffering from either the chronic or the acute form of HAT. Both proteins were significantly increased ( p < 0.0001) in the CSF of rhodesiense HAT patients. These findings contribute in better understanding the pathophysiological mechanisms of late stage HAT caused by T . b . gambiense or T . b . rhodesiense and pave the way for further investigations on the clinical significance of CRP and ORM1. Mass spectrometry data are available via ProteomeXchange (identifier PXD001082).